Prenatal exposure to extra vitamin D from fortification and risk of developing coeliac disease. (13th November 2019) - Moos, C; Duus, K S; Frederiksen, P; Heitmann, B; Andersen, V
Abstract: Introduction: Few studies have examined the role of maternal diet in relation to development of autoimmune diseases such as coeliac disease (CD). In Denmark, cancellation of mandatory vitamin D fortification of margarine in June 1985 provides this opportunity. This study examined if prenatal exposure to extra vitamin D from food fortification or season of birth were associated with a decreased risk of developing CD later in life. If low prenatal vitamin D levels are a risk factor, there are immediate, cheap and easy public health implications. Methods: This register based study has a partially ecologic design. The two entire cohorts were created using information available from the Danish birth registry and development of CD (ICD-8 269 ICD-10 K90) over 30 years was retrieved from the Danish National Patient Register. Logistic regression analysis was used to generate odds ratios and 95% confidence intervals. Results: There was a lower odds ratio of developing CD (OR: 0.811 95% CI 0.655; 1.003) from the exposed birth cohort adjusting for sex and season of birth. There was a significant season effect particularly for children born in autumn (OR 1.6 95% CI 1.16; 2.21) and born summer (OR 1.5 95% CI 1.1;2.1) when compared to children born in winter. Conclusions: The results indicate a potential protective effect of a small extra intake of vitamin D from food fortification by pregnant women in relation to the risk of their offspring developing CD. This conclusion is further supported by the results showing that summer born children, where first half of gestation occurred during the dark winter season, had a higher risk of CD. This research lends support for the reconsideration of vitamin-D food fortification in Denmark. Key messages: Exposure to even a small amount of vitamin D prenatally may protect against developing coeliac disease later in life. Association between season and CD indicates that vitamin D may play an important role in relation to fetal programming.